Design and rationale of the tobacco, exercise and diet messages (TEXT ME) trial of a text message-based intervention for ongoing prevention of cardiovascular disease in people with coronary disease: a randomised controlled trial protocol. Issue 1 (19th January 2012) - Chow, C K; Redfern, J; Thiagalingam, A; Jan, S; Whittaker, R; Hackett, M; Graves, N; Mooney, J; Hillis, G S
Abstract : Background: Although supporting lifestyle change is an effective way of preventing further events in people with cardiovascular disease, providing access to such interventions is a major challenge. This study aims to investigate whether simple reminders about behaviour change sent via mobile phone text message decrease cardiovascular risk. Methods and analysis: Randomised controlled trial with 6 months of follow-up to evaluate the feasibility, acceptability and effect on cardiovascular risk of repeated lifestyle reminders sent via mobile phone text messages compared to usual care. A total of 720 patients with coronary artery disease will be randomised to either standard care or the TEXT ME intervention. The intervention group will receive multiple weekly text messages that provide information, motivation, support to quit smoking (if relevant) and recommendations for healthy diets and exercise. The primary end point is a change in plasma low-density lipoprotein cholesterol at 6 months. Secondary end points include a change in systolic blood pressure, smoking status, quality of life, medication adherence, waist circumference, physical activity levels, nutritional status and mood at 6 months. Process outcomes related to acceptability and feasibility of TEXT ME will also be collected. Ethics and dissemination: Primary ethics approval was received from Western Sydney Local Health Network Human Research Ethics Committee—Westmead. Results will be disseminated via the usual scientific forums including peer-reviewed publications and presentations at international conferences. Clinical trials registration number: ACTRN12611000161921.